Małżeństwo w językowym obrazie świata. Na przykładzie paremii w języku polskim, rosyjskim i angielskim - Katarzyna Kuligowska (Studia Rossica Posnaniensia)
The essence of marriage is being widely discussed in the last few decades in many social circles and at many different levels. From the linguistic point of view it is usually characterised on the basis of man’s and woman’s roles in their relationship. The aim of the paper is to present the view of marriage in Polish, Russian and English proverbial phrases. For the purposes of the article about 350 Polish and Russian and about 300 English proverbs have been subjected to cognitive analysis. The research proves that the concept of marriage is roughly universal in all three languages and it presents definitely an androcentric perspective. Wives in proverbs are shown in a very unfavourable light as grouchy, quarrelsome, unfaithful and narrow-minded human beings. Marriage reflected in sayings is usually a burden which diminishes man’s happiness and may even lead to his sickness, fast aging and death. What is more, quite a lot of proverbial phrases in all three languages under study foster violence against women. The concept of marriage presented in proverbs is undoubtedly a reflection of the old way of thinking and the old system of values, but the preliminary research of anti-proverbs, i.e. more modern expressions, proves that it has not undergone any fundamental changes in the language awareness of the Polish, Russian and English native speakers.